STUDENTS’ ATTITUDES CONCERNING LECTURER’S CORRECTIVE FEEDBACK IN TEACHING WRITING - Muhammad Iqbal Ripo Putra, Sulaiman (Jurnal Pendidikan Bahasa, 2016)
This research aims to explore and describe whether there is an inexpediency of the students’ perception against the feedback which can affect the teaching pedagogy in implementing it. In accord to this, this research explores more about the students’ attitudes in different levels of proficiency in writing. This research was conducted at IKIP PGRI Pontianak. A qualitative case study approach was employed and the data were taken through close questionnaire, in-depth interview, observation, and document. In analyzing the data, the interactive model of data analysis proposed by Miles and Huberman was used. Based on the synergistic findings demonstrate that: (1) the different levels of proficiency in writing do not affect the attitudes of the students as the informants. Most of the informants (the students) have positive attitudes towards teachers’ corrective feedback; (2) the attitudes of the students affect their achievement in writing English. The major recommendations are that lecturers should carefully scrutinize target language features; practice a variety of suitable corrective feedback; and cater for individual students’ specific needs.  Keywords:  students’ attitudes, corrective feedback, teaching writing.